Kaimakli Gardens - Panayides, Omiros (My University, 2026)
Sociologist Christiana Stylianou and photographer Nicos Philippou engaged in a visual ethnographic process in the historically working class suburb of Kaimakli documenting local’s relationship with their yards, gardens and plants with an emphasis on those they use in their cooking. The process accounted for the changing demographics of Kaimakli and it’s enrichment with a community of artists and intellectuals that moved into the suburb during the last couple of decades as well as migrants fleeing war and economic hardship elsewhere. The material gathered in the process is collected here in the form of this “DIY” chapbook which functions as a poetic inventory of these plants as well as the stories people share about them and as a tribute to our collective love affair with gardening.